Oculomotor differences in adults with and without probable developmental coordination disorder - Sumner, Emma; Hill, Elisabeth L. (Frontiers in Human Neuroscience, 2024)
Adults with Developmental Coordination Disorder (DCD), sometimes referred to as dyspraxia, experience difficulties in motor development and coordination, impacting on all aspects of their daily lives. Surprisingly little is known about the mechanisms underlying the difficulties they experience in the motor domain. In childhood DCD, aspects of oculomotor control have been shown to be altered. The purpose of this study was to determine whether oculomotor differences are present in adults with and without probable DCD. Visual fixation stability, smooth pursuit, and pro- and anti-saccade performance were assessed in 21 adults (mean 29 years) with probable DCD/dyspraxia (pDCD) and 21 typically-developing (TD) adults (mean 21 years). Eye tracking technology revealed that oculomotor response preparation in the pro-and anti-saccade tasks was comparable across groups, as was pursuit gain in the slower of the two smooth pursuit tasks. However, adults with pDCD made significantly more saccades away from the fixation target than those without DCD and significantly more anti-saccade errors. Further, compared to TD adults, adults with pDCD demonstrated difficulties in maintaining engagement and had lower pursuit gain in the faster pursuit task. This suggests that adults with pDCD have problems with saccadic inhibition and maintaining attention on a visual target. Since this pattern of results has also been reported in children with DCD, oculomotor difficulties may be persistent across the lifespan. An awareness of the lifelong impact of atypical oculomotor control in activities of daily living would support clearer understanding of the causes and impacts of these difficulties for those with DCD.